2023
DOI: 10.1097/lbr.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Ultrasound-guided Mediastinal Lymph Nodal Cryobiopsy in Patients With Nondiagnostic/Inadequate Rapid On-site Evaluation

Abstract: Background: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is considered the investigation of choice for sampling mediastinal nodes. A major drawback of EBUS-TBNA is its lower diagnostic yield for lymphoma and benign diseases. EBUS-guided mediastinal cryobiopsy (EBUS-MCB) is a novel technique that provides larger nodal biopsy samples, with an acceptable safety profile. In this study, we aimed to evaluate the diagnostic yield of EBUS-MCB in patients with an inconclusive rapid on-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In Maturu et al ( 12 ), EBUS-TMC confirmed diagnoses in 33 cases (71.7%). In 14 cases with inadequate ROSE that subsequently underwent EBUS-TMC, malignancy was confirmed by both EBUS-TMC and EBUS-TBNA.…”
Section: Diagnostic Yield In Malignancymentioning
confidence: 88%
See 1 more Smart Citation
“…In Maturu et al ( 12 ), EBUS-TMC confirmed diagnoses in 33 cases (71.7%). In 14 cases with inadequate ROSE that subsequently underwent EBUS-TMC, malignancy was confirmed by both EBUS-TMC and EBUS-TBNA.…”
Section: Diagnostic Yield In Malignancymentioning
confidence: 88%
“…Ariza-Prota et al ( 11 ) conducted a prospective study in Spain on 50 patients, wherein participants underwent EBUS-TBNA followed by EBUS-TMC. Maturu et al ( 12 ) carried out a prospective study on 46 patients in India, in which EBUS-TMC was conducted if rapid on-site evaluation (ROSE) during EBUS-TBNA yielded insufficient or inconclusive results. A prospective study in Israel documented EBUS-TMC in 24 patients ( 13 ) and two case reviews have been conducted, one on four patients ( 14 ) and one on five patients ( 15 ).…”
Section: Studiesmentioning
confidence: 99%
“…Endobronchial ultrasound-guided transbronchial lymph node cryobiopsy (EBUS-TBLCB) involves a similar technique as EBUS-IFB where a hole is first created in the airway for advancement of the cryoprobe. Multiple tools have been reported for this purpose, including needles with various gauges, electrocautery knife and Nd YAG Laser [60 ▪ ,61 ▪▪ ,62,63,64 ▪▪ ,65]. After freezing, the cryoprobe and EBUS scope are removed in block for specimen retrieval (Fig.…”
Section: Tissue Acquisition: How To Get Enough?mentioning
confidence: 99%
“…Maturu et al . [64 ▪▪ ] performed EBUS-TBLCB when ROSE was nondiagnostic or inconclusive. The additive diagnostic yield of cryobiopsy was 43.7% in 32 patients with nondiagnostic ROSE and cryobiopsy was the only diagnostic modality in 14 patients with primarily nonmalignant conditions, like prior studies [64 ▪▪ ].…”
Section: Tissue Acquisition: How To Get Enough?mentioning
confidence: 99%
See 1 more Smart Citation